Respostas

2013-11-25T11:53:08-02:00
A) 3x + y = 8
     x - 3y = 6 
y = 8 - 3x
Substituindo:
x - 3 (8 - 3x) = 6
x - 24 + 9x = 6
x + 9x = 6 + 24
10x = 30
x = 30 ÷ 10
x = 3
Vamos encontrar o valor de y.
y = 8 - 3x
Substituindo:
y = 8 - 3 * 3
y = 8 - 9
y = - 1
Resposta: x = 3     e      y = - 1

b) x + 5y = 0
    4x - y = 21
x = 0 - 5y
Substituindo:
4 (0 - 5y) - y = 21
0 - 20y - y = 21
- 21y = 21
y = 21 ÷ (- 21)
y = - 1
Vamos encontrar o valor de x.
x = 0 - 5y
Substituindo:
x = 0 - 5 (- 1)
x = 0 + 5
x = 5
Resposta: x = 5    e     y = - 1
vallw muito obg !!
De nada!
o que significa essa estrelinha *